Solution
We have the following system of equations given:
2x - 3y = 21 (1)
-6x +2y = 7 (2)
Part a
We can multiple the first equation by 3 and we can add the result to equation (2) and we have:
6x -9y = 63
-6x +2y =7
____________
-7y = 70
y= 70/-7 = -10
Part b
We can multiply the first equation by 2/3 and we can add the result to the second equation and we got:
4/3x - 2y = 14
-6x +2y= 7
____________
-14/3 x = 21
x= -9/2 = -4.5
Part c
We can use other methods for example substitution in order to solve the problem. For example we can solve for x in the first equation and we have:
And replacing in the second one we got:
And after solve for x and y we got:
x= -9/2
y = -10